2023
DOI: 10.1021/acsomega.2c07743
|View full text |Cite
|
Sign up to set email alerts
|

Designing Excess Electron Compounds by Substituting Alkali Metals to a Small and Versatile Tetracyclic Framework: A Theoretical Perspective

Abstract: Organic compound-based nonlinear optical (NLO) materials have sparked a lot of attention due to their multitude of applications and shorter optical response times than those of inorganic NLO materials. In the present investigation, we designed exo-exo-tetracyclo[6.2.1.1 3,6 .0 2,7 ]dodecane (TCD) derivatives, which were obtained by replacing H atoms of methylene bridge carbon with alkali metals (Li, Na, and K). It was observed that upon the substitution of alkali metals at bridging CH 2 carbon, absorption with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Overall, it is observed that the values of β o obtained at the M06-2X/6-311+G­(d,p) level of theory are comparable to the values obtained at CAM-B3LYP, BHandHLYP, WB97XD, APFD, and B97D functionals. These additionally computed results support our results computed at M06-2X/6-311+G­(d,p) level of theory with some degree of nonconsistency …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, it is observed that the values of β o obtained at the M06-2X/6-311+G­(d,p) level of theory are comparable to the values obtained at CAM-B3LYP, BHandHLYP, WB97XD, APFD, and B97D functionals. These additionally computed results support our results computed at M06-2X/6-311+G­(d,p) level of theory with some degree of nonconsistency …”
Section: Resultssupporting
confidence: 90%
“…These additionally computed results support our results computed at M06-2X/6-311+G-(d,p) level of theory with some degree of nonconsistency. 57…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 99%
“…Various molecular frameworks are known in literature that exhibit nonlinear optical response such as diffuse excess electron, [70,71] push pull, [72] metal organic fragments (MOFs), [73] octupolar molecules [74] and so forth. Push pull based dyes with promising donor, π-bridge, and acceptor moieties were generally show nonlinear optical activity due to noncentrosymmetric nature of molecules.…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 99%